Effects of Current Density on Nociceptor Activation Upon Electrical Stimulation in Humans. Issue 3 (14th September 2015) - Landmann, Gunther; Stockinger, Lenka; Lustenberger, Corinne; Schmelz, Martin; Rukwied, Roman
Abstract: Objectives: Mechano‐insensitive ("silent") nociceptors contribute to neuropathic pain. Their activation causes an axon‐reflex erythema, but their high electrical excitation thresholds complicate their assessment, particularly in painful neuropathy. We therefore developed electrical stimulation paradigms for brief nociceptor activation and explored their sensitivity for clinical trials. Method: The local ethics committee approved the study protocol, and 14 healthy subjects were enrolled. Electrical stimuli were administered to ventral forearm and dorsum of the foot via self‐adhesive 3 × 10 mm electrodes and a pair of blunted 0.4‐mm‐diameter platinum/iridium pin electrodes. Pain thresholds were determined and nociceptors activated at 1.5‐fold pain threshold by 5 blocks delivering 10 pulses each and at randomized frequencies of 5 to 10 to 20 to 50 to 100 Hz, respectively. Axon reflex erythema and pain were recorded. Results: Increased frequencies dose‐dependently increased pain ( P < 0.0001). Pin electrode stimulation was more painful than adhesive electrode stimulation ( P < 0.04) particularly at the feet. Axon reflex erythema was significantly smaller at the feet than at the forearm ( P < 0.0001). At both skin sites, pin electrode stimuli evoked significantly larger erythema ( P < 0.05). Conclusions: Electrical stimulation at high current density using pin electrodes is a sensitive method for investigating "silent" nociceptors, which might therefore preferably be applied in neuropathic pain conditions.